Production and Characterization of Indium Oxide and Indium Nitride - Luis C. Jimenez B. (Brazilian Journal of Physics, 2006)
Thin films of indium oxide 200 nm thick and indium nitride 150 nm thick were produced by reactive sputteringdeposition onto soda lime substrates. The Indium cathode was kept under vacuum attached to a high voltagedc. The InxOy films were obtained in argon-oxygen mixture with total pressure between 2 and 7 Pa, currentdensity between 0.04 and 0.56 mA/cm2 and substrate temperature of 300 K. The InxNy films were obtained inargon-nitrogen mixture with total pressure between 1 and 5 Pa, current density between 0.18 and 14 mA/cm2and substrate temperature of 320 K. Results revealed that thin films give rise to high conductivity, are transparentand have a carrier density of 1019 cm¡3 for InxOy and 1017 cm¡3 for InxNy. These results were obtained mainlyfrom temperature dependent a and s measurements. The reduced chemical potential was calculated consideringthree different scattering mechanisms i.e. interaction with optically polarized phonons, interaction with ionizedimpurities and interaction with grains, in order to identify the main scattering mechanism, which resulted to bedue to impurities.